Optimization of 'halia putih' (Zingiber Officinale Rosc. Var Officinale) extract on beef and chicken fat reduction / Azizah Mohamad - Mohamad, Azizah (2005)
The purpose of this study was to obtain the optimum condition of ginger extract on the maximum fat reduction on beef and chicken. Type of ginger chosen was 'halia putih' or its scientific name was Zingiber Officinale Rose. Var Officinale. Beef and chicken were treated with ginger extract which different concentrations ranging from 20% to 100% for 5 to 25 minutes of immersion time in shaking water bath at temperature from 30°C to 70°C. Experimental design was created by using Minitab Software version 13. Total fat content of beef and chicken were determined by Werner-Schmid method before and after treatment with ginger extract. Beef and chicken treated with 'halia putih' showed the maximum reduction of fat content. It was found that the optimum conditions for 'halia putih' extract to obtain the maximum reduction of fat content in beef and chicken were 60% ginger extract concentration for 15 minutes of immersion time at temperature 30°C and 80% ginger extract concentration for 20 minutes of immersion time at temperature 60°C respectively.